Effects of Social Ties in Knowledge Diffusion: case study on PLOS ONE - Eltermann, Felipe; Godoy, Alan; Von Zuben, Fernando J. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM); 2016: Anais do V Brazilian Workshop on Social Network Analysis and Mining, 2016)
In order to capture the effects of social ties in knowledge diffusion, this paper examines the publication network that emerges from the collaboration of researchers, using citation information as means to estimate knowledge flow. For this purpose, we analyzed the papers published in the PLOS ONE journal finding strong evidence to support that the closer two authors are in the co-authorship network, the larger the probability that knowledge flow will occur between them. Moreover, we also found that when it comes to knowledge diffusion, strong co-authorship proximity is more determinant than geographic proximity.